A Certain Class of Harmonic Mappings Related to Functions of Bounded Boundary Rotation - Yavuz Duman, Emel; Aydoğan, Melike; POLATOĞLU, YAŞAR (Eudoxus Press, Llc, 1424 Beaver Trail Drive, Cordova, Tn 38016 Usa, 2014)
Let V(k) be the class of functions with bounded boundary rotation and let S-H be the class of sense-preserving harmonic mappings. In the present paper we investigate a certain class of harmonic mappings related to the function of bounded boundary rotation.
Keywords: Bounded boundary rotation; harmonic mappings; complex dilatation; growth and distortion theorems